GIS-based scenarios for the reorganization of Kansas counties - Peterson, Rorik Ford (Kansas State University, 2008)
County consolidation and reorganization has been rare in the United States in the last 100 years, and recent literature on county consolidation and reorganization is limited. Still, county consolidation appears to be a possible method for reducing the cost of government in areas with declining rural populations. Seven consolidation scenarios were generated for Kansas using criteria based on distance from a county seat, population distribution, and local economic strength in terms of tangible assessed valuation. All the scenarios reduce the number of counties from the current 105 to 25. The goal of the study was not to advocate or oppose county consolidation, but rather to show a proficiency of GIS to implement user-defined consolidation and reorganization procedures. The seven scenarios each possessed strengths and weaknesses based on appearance and statistical measures of area and population. The population scenarios possessed the greatest apparent strength, based on measures of area and population as well as overall appearance. Still, county consolidation and reorganization is a daunting task due to inertia and the social opposition that would likely result, due to loss of existing county identity and losses of government funding provided to numerous rural county seats.
Keywords: consolidation; Kansas; counties; Geography (0366); Political Science, General (0615); Political Science, Public Administration (0617)